1986
DOI: 10.1002/ajpa.1330690108
|View full text |Cite
|
Sign up to set email alerts
|

An enigmatic hypoplastic defect of the deciduous canine

Abstract: A roughly circular hypoplastic defect restricted to the labial enamel surface of the deciduous canine is described. This pathology is quite common in available samples of Upper Paleolithic and Neolithic children and a cadaver sample of recent Calcuttans, affecting 44% to 70% of individuals. It is rare in a Neanderthal sample and in children from a clinical practice in Vancouver. The lesion occurs twice as commonly in the lower jaw. The defect appears to commence at or after birth owing to localized pressure on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 24 publications
3
74
0
5
Order By: Relevance
“…This suggests that differences in nutritional status, or obstetric and paediatric care, may be important aetiological factors. 1,6,8 Skinner 4 has looked at the onset and duration of the lesion in detail and notes that the time interval during which a specific defect formed can be determined by relating the height of the defect to rates of deciduous canine formation. An intermediate formation rate for the deciduous canine is 0.33 mm per month, corresponding to an average time of 5.2 months for the form ation of the defect.…”
Section: Australian Dental Journal 2000;45:(2):83-90mentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that differences in nutritional status, or obstetric and paediatric care, may be important aetiological factors. 1,6,8 Skinner 4 has looked at the onset and duration of the lesion in detail and notes that the time interval during which a specific defect formed can be determined by relating the height of the defect to rates of deciduous canine formation. An intermediate formation rate for the deciduous canine is 0.33 mm per month, corresponding to an average time of 5.2 months for the form ation of the defect.…”
Section: Australian Dental Journal 2000;45:(2):83-90mentioning
confidence: 99%
“…Skinner 4 further suggested that minor trauma to the developing canine crown of neonates (for example, sharp objects placed in the mouth) is an important environmental factor. At birth the cortical bone forming the labial bulge of the crypt of the primary canine is either thin or absent, and thus the crown may not receive adequate protection from early physical trauma (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LEH and pitpatch hypoplasia were observed in the permanent teeth of the Damdama skeletons, LHPC was observed in the only sub-adult with deciduous teeth (DDM 5). Following a pattern of expression commonly observed in clinical studies of the trait, the maxillary canines were unaffected while both mandibular canines exhibited this 'plane-form' type of EH (Skinner andHung, 1986, 1989;Hillson and Bond, 1997). The labial surface of mandibular right and left primary canines were affected though the defects exhibited significant asymmetry in trait expression ( Figure 5); the number, size, and location of defects were different in antimeres.…”
Section: Dental Pathology: Enamel Hypoplasia and Health Statusmentioning
confidence: 72%
“…Linear enamel hypoplasia (LEH) is the most commonly observed and studied form of EH and more frequently affects permanent than deciduous teeth (Goodman and Rose, 1990). Other expressions of enamel hypoplasia include depressed areas of enamel known as 'pit-patches' (Goodman et al, 1992), cuspal enamel hypoplasia of molar teeth (Ogden, 2008), and LHPC (Skinner, 1986). Although LEH and pitpatch hypoplasia were observed in the permanent teeth of the Damdama skeletons, LHPC was observed in the only sub-adult with deciduous teeth (DDM 5).…”
Section: Dental Pathology: Enamel Hypoplasia and Health Statusmentioning
confidence: 99%